Biscuit Formulation Substitutes Wheat Flour with Tempeh Flour and Nile Tilapia Fish Flour as Complementary Food to Prevent Stunting - kasyani, Kasyani; Perdana, Silvia Mawarti; Ibnu, Ismi Nurwaqiah; Kusmawan, David; Lanita, Usi; Alfridsyah, Alfridsyah; Wazzan, Huda; Mursyid, Mursyid (Department of Technology of Agricultural product (THP) Jambi University, 2025)
Abstract— Stunting is one of the nutritional problems in Indonesia. One of the specific interventions for stunting is nutritional support in the form of protein-rich complementary foods, both animal and plant-based protein. This research is expected to provide an alternative to high-protein complementary foods for toddlers, thereby contributing to efforts to reduce stunting problems in Indonesia. The biscuit formulation consists of four treatments of the ratio of wheat flour: tempeh flour: Nile Tilapia fish flour, namely (F1) 100:0:0, (F2) 50:15:35, (F3) 50:25:25, and (F4) 50:35:15. The test parameters in this study were organoleptic tests, chemical tests in the form of proximate analysis, calcium, zinc, dietary fiber, amino acid, and fatty acid content, as well as physical tests in the form of texture and color. The results of the study showed that the best treatment based on the organoleptic test was a ratio of 50:25:25. Chemical tests showed that proximate analysis, calcium, dietary fiber, essential and non-essential amino acid composition, and fatty acid composition of selected biscuits were higher than those of control biscuits. The zinc content of selected biscuits was the same as that of control biscuits. The results of physical tests showed that selected biscuits had the same color description as the control, but had a softer texture than the control. The conclusion obtained was that, based on the composition of nutritional and non-nutritional content, selected biscuits with a 50:25:25 formulation have the potential as complementary food ingredients for breast milk that can help prevent stunting in toddlers.